2016
DOI: 10.1128/genomea.01020-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Streptomyces clavuligerus F613-1, an Industrial Producer of Clavulanic Acid

Abstract: Streptomyces clavuligerus strain F613-1 is an industrial strain with high-yield clavulanic acid production. In this study, the complete genome sequence of S. clavuligerus strain F613-1 was determined, including one linear chromosome and one linear plasmid, carrying numerous sets of genes involving in the biosynthesis of clavulanic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The genome of the strain F613-1 has been sequenced and assembled (Cao et al 2016). Genome annotation was previously performed as recommended by the NCBI (National Center for Biotechnology Information) online pipeline for prokaryotic species.…”
Section: Genome Annotation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of the strain F613-1 has been sequenced and assembled (Cao et al 2016). Genome annotation was previously performed as recommended by the NCBI (National Center for Biotechnology Information) online pipeline for prokaryotic species.…”
Section: Genome Annotation and Analysismentioning
confidence: 99%
“…Streptomyces clavuligerus strain F613-1 is an important industrial producer with high clavulanic acid production, but poor ability to produce 5S clavam compounds, and its complete genome of F613-1 has been sequenced (Cao et al 2016). In this study, we analyzed the compact genome sequence of F613-1, which contains a 6.78 Mb chromosome, considerably smaller than other reported S. clavuligerus genomes, and a 707 Kb pSCL4-like plasmid (smaller than 1.8 Mb pSCL4, however, carrying the intact paralog gene cluster related with biosynthesis of clavulanic acid).…”
Section: Introductionmentioning
confidence: 99%
“…Streptomyces clavuligerus F613-1 is an industrial CA producer, and its complete genome sequence has been reported (Cao et al, 2016). The putative TCS CagRS is located near the CA biosynthetic gene cluster in F613-1 (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…TCSs not only respond to changes in environmental factors, but in Streptomyces , also influence development and secondary metabolism such as antibiotic production (Mendes et al, 2007). S. clavuligerus F613-1 is an industrial CA producer strain, and we have previously reported the complete genome sequence of this strain (Cao et al, 2016). In this study, we identified TCS CagRS, which is annotated as orf22/orf23 in S. clavuligerus 27064 (Song et al, 2009) and which is close to the CA biosynthetic gene cluster in F613-1.…”
Section: Introductionmentioning
confidence: 99%
“…These plasmids can recombine with the chromosome, enhancing the genetic interchange of secondary metabolites (Medema et al, ). Interestingly, S. cattleya NRRL 3841 and S. lipmannii NRRL 3584 are two species of the genus lacking plasmids (Netolitzky, Wu, Jensen, & Roy, ), and even the strain S. clavuligerus F613‐1 has a different number of plasmids (Cao et al, ). These findings suggest that plasmids could provide a vehicle for genetic interchange by horizontal gene transfer or some other mechanism in this species and even in the genus.…”
Section: Introductionmentioning
confidence: 99%